Do Remuneration Committees at UK Corporate Banks Exploit the use of Compensation Peer Groups as a Mechanism to Inflate CEO Pay? - Arnold, Ben (2013)
Executive compensation within banking has received much attention from academics, politicians, the media and the general public in the light of the recent financial crisis whereby many financial institutions’ market capitalisation has fallen dramatically whilst their CEO’s remain to walk away with large remuneration packages. Although pay arrangements are being scrutinized by these wider commentators to a greater degree, no consensus on the underlying reasons explaining an apparent disconnect between bank performance and CEO pay has been reached. The use of compensation peer groups as a mechanism to allocate pay is widespread across many industries, including banking. Many academics have looked at the effectiveness of compensation peer groups, however the work is predominantly US based and this paper seeks to be the first to look specifically at the UK’s largest corporate banks from 2004-2011. Using a completely original data set collected manually through Annual Reports alongside Datastream and Bankscope, an attempt has been made to test whether the remuneration committees at the UK’s 10 largest corporate banks have been using peer groups as a way to exploit rising pay levels, or whether they are genuinely being used as an effective method to assess CEO performance. Using the Total Shareholder Return performance for the sample of 10 banks, as well as the Total Return Index for the Global FTSE and UK FTSE bank indexes, a multiple linear regression model has been able to test peer group strength following peer movements over the period. The results indicate that across our sample peer movements actually increased peer group strength in comparison to the rest of the market, indicating that remuneration committees have made sound judgements with regards to the composition of compensation peer groups, hence no evidence of manipulation being found. Keywords: Executive Compensation, Remuneration Committees, Compensation Peer Groups, Optimal Contracting Model, Managerial Power Hypothesis